Cross-country evidence on the distributional impact of fiscal policy. Issue 51 (2nd November 2018) - Salotti, Simone; Trecroci, Carmine
ABSTRACT: This article provides new evidence on the distributional effects of fiscal policy using data on a panel of OECD economies over the last four decades. We study how four measures of income inequality and poverty respond to several stock and flow variables accounting for fiscal actions. We find that increases in government debt and expenditure promote a less unequal distribution of income. We detect a significant distributional impact of education and social spending as well as of government consumption expenditure. We also investigate potential redistributive implications of large fiscal expansion and consolidation episodes finding no evidence of additional effects beyond those associated with conventional fiscal variables. Abbreviations: OECD: Organisation for Economic Co-operation and Development; GDP: Gross Domestic Product; G20: Group of 20 economies (forum of 19 dvanced and emerging countries plus the European Union); CGE: Computational General Equilibrium models; DSGE: Dynamic Stochastic General Equilibrium models; UN-WIDER: United Nations World Institute for Development Economics Research; SWIID: Standardized World Income Inequality Database; WDI: World Development Indicators; PPP: Purchasing-Power Parity; LIS: Luxembourg Income Database; GMM: Generalized Method of Moments; FE: Fixed Effects; RE: Random Effects; SE: Standard Errors; CPI: Consumer Price Index